Respuesta :
The rule is [tex]a \sqrt{b}+c \sqrt{b}=(a+c) \sqrt{b} [/tex], so
[tex]4 \sqrt{5}+2 \sqrt{5} = 6 \sqrt{5} [/tex]
[tex]4 \sqrt{5}+2 \sqrt{5} = 6 \sqrt{5} [/tex]
Answer:
[tex]6\sqrt{5}[/tex]
Step-by-step explanation:
sum of 4 sqrt 5 + 2 sqrt 5
[tex]4\sqrt{5} + 2\sqrt{5}[/tex]
Both terms have same square root(5)
So they are like terms.
When they are like terms, we add the number outside the square root.
Square root remains the same.
[tex]a\sqrt{x} + b\sqrt{x}=(a+b)\sqrt{x} [/tex]
[tex]4\sqrt{5} + 2\sqrt{5}=(4+2)\sqrt{5}=6\sqrt{5}[/tex]